Improved shear strength design of cold-formed steel connection with single self-piercing rivet. (October 2018) - Xie, Zhiqiang; Yan, Weiming; Yu, Cheng; Mu, Tingting; Song, Linlin
Abstract: In order to introduce self-piercing rivet (SPR) technique to component connections of thin-walled steel structures, 78 SPR joints were tested to evaluate their quality and the shear strength. Parameters included in this test program were the sheet thickness, and the rivet. Based on test results, the research developed an empirical formula between the combination thicknesses of sheet and rivet length, and proposed quality evaluation standard of SPR connections and a new design method of shear strength. The test results showed that sheet thickness and sheet thickness ratio had a great effect on failure mode, and rivet length was a key factor on shear properties of SPR connections. The proposed quality evolution standard and design calculation method of shear strength in this paper had certain reasonability and reliability. Highlights: Pilot research on self-piercing rivet connections in cold-formed steel structures. Extensive test matrix to address a large variation of connection configurations and failure modes. Recommendation for appropriate details of self-piercing rivet connections for cold-formed steel structures is developed. Improved design method of shear strength for self-piercing rivet connections in cold-formed steel structures is proposed.